WSMO-Lite based web service discovery algorithm for mobile environment - Saadon, Nor Azizah (SCRG Publication, 2014)
The advancement of mobile and wireless technologies has led to widespread access of web services in a mobile environment, where mobile devices can host web service as a web service provider or service requester. Due to rapid proliferation of web services with similar functionalities, discovering appropriate mobile web services that match service requester is still a major obstruction to its advancement, especially with the stringent constraints currently relating to mobile devices. This paper proposes an enhancement of WSMO-Lite to describe Non-Functional Properties (NFPs) as a context and Quality of Web Service (QoWS) information for mobile computing environment targeted to support the discovery of web services in a mobile environment. Then, the similarity of the service requester with each of the offered services is measured using semantic matchmaking algorithm based on WSMO-Lite was proposed. As a lightweight semantic web service description language, WSMO-Lite improves flexibility of web service description and enhances the web service discovery mechanism. The applicability of the enhancement and algorithm is applied through a simple case study to demonstrate the effectiveness of the idea.